Potencial imunomodulador e antimicrobiano do (+)-a-pineno e (+)-β-pineno - Costa, Davi Felipe Neves (2017)
Pinenos, constituents of several essential oils, have roused interest of the scientific community, for the anti-inflammatory and antimicrobial potential. The present study evaluated the immunomodulatory potential of (+) - α-pinene and (+) - β-pinene enantiomers in human leukocytes and their antimicrobial activity on Streptococcus mutans and Escherichia coli species. The results showed that concentrations of (+) - α-pinene and (+) - β-pinene, equal to or less than 900μM and 450μM respectively, were not cytotoxic in PBMCs cells and that these phytochemicals inhibited the formation of ROS in PMN cells. The MIC values of (+) - α-pinene for S. mutans and E. coli were 3600μM and 450μM respectively whereas for (+) - β-pinene were 1800μM and 225μM. It is concluded that the compounds tested have antimicrobial activity against the tested strains and inhibit ROS production.